145+36w=433

Simple and best practice solution for 145+36w=433 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 145+36w=433 equation:


Simplifying
145 + 36w = 433

Solving
145 + 36w = 433

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-145' to each side of the equation.
145 + -145 + 36w = 433 + -145

Combine like terms: 145 + -145 = 0
0 + 36w = 433 + -145
36w = 433 + -145

Combine like terms: 433 + -145 = 288
36w = 288

Divide each side by '36'.
w = 8

Simplifying
w = 8

See similar equations:

| x-9y=-81 | | -6=-(x+10) | | 1/6x+3/4=5/9 | | 2b+17=11 | | -3=-3x+15 | | 42=96 | | 4-2/3(4x-9)=111 | | 2b-9=2b-9 | | -2(x-2)=26 | | 4x+23=-1 | | -3/2(x+4)-3-7 | | 5x+5=130 | | 6c^2-16c+2=0 | | a+36=7a | | 12+3h=30 | | 3+x+y+12= | | X+X+10+X+15=575 | | 11/2+21/2= | | 6(x-3)+13(x+10)= | | 4-10t=-6-8t | | 14x-7=75 | | 288=-16t^2+96t | | 2x+4=10-x | | -1/5x+15=-x+3 | | 15p=-5 | | 3/4=4m-1/6 | | X+X+24=106 | | 2(8s+8)-4s=3(4s+5)-18 | | (3x+15)-8= | | 4(-3y+7)-2y=0 | | 3x/5=-9 | | 10x-1=7x+14 |

Equations solver categories